Attitudes of citizens of the United States, the Unidet Kingdom, and Turkey in permits requested by mobile apps - Öçlü, Burak (My University, 2020)
Learning Overview: After attending this presentation, attendees will be able to understand the relationship between risk, privacy and mobile risk attitudes of citizens of different countries and interpret this in terms of mobile application permissions. Impact on the Forensic Science Community: This presentation will impact, the forensic science community by informing about the difference between attitudes in daily life and the actual situation that occur according to the data security risks that may arise. How to secure this information has become an important problem as application-maker firms have increased their access to personal data. In this context, our research aims to establish the relationship between risk, privacy and mobile risk attitudes of people living in different countries. For the purpose, a survey of 26 questions was conducted for citizens living in the USA, UK and Turkey, provided that there were 150 people from each country (in total 450 people). Surveys of their native languages were conducted for participants in all countries. The survey consists of multiple-choice questions with questions consisting of a Likert scale of 5s. Hypotheses are " HOa: there is no relationship between the risk attitude and the privacy attitude.” and “HOb: there is no relationship between the privacy attitude and mobile risk attitude." and "HOc: there is no relationship between risk attitude and mobile risk attitude." in the study. Within the scope of this research, “HOa” and “HOb” rejected and strong positive relationship in the USA, weak positive relationship in the UK and moderate positive relationship in Turkey were identified. “HOc” also rejected and found that a moderate positive relationship in the USA and UK and a weak positive relationship in Turkey. Participants were asked which of the 9 different types of mobile application permission request options they would not want to grant access to. As a result of the research, the most unwanted permission to be given in the US was “location information” and “access to SMS records” in the UK and “phone call records” in Turkey. According to the results of the research, 55.33, 48, 87.39 percent of respondents in the USA, UK and Turkey stated that they are using Instagram application, while respectively 54.21, 68.05, 46.56 percent of users have declared that they will not allow downloads for the application if they see the permissions requested by the application without specifying the application name. Respectively, 19.33, 70, 95.30 percent of respondents in the USA, UK and Turkey stated that they are using the WhatsApp app, while respectively 34.48, 63.80 and 46.85 percent declared that they would not download the app with current permission. Respectively, 28.67, 39.33, 22 percent of respondents in the USA, UK and Turkey stated that they are using the Spotify app, while respectively 55.81, 55.93 and 42.42 percent declared that they would not download the app with current permission. Although the real estate application is different in each country, respectively 12, 10, 16 percent of the respondents in the USA, UK, Turkey said they are using the real estate application, while respectively 50, 80, 70.80 percent of these users have declared that they will not download the current permissions When the results are examined, all hypotheses are accepted for all countries and it means that there was a positive relationship between “risk, privacy and mobile risk attitude”. In addition, the permissions that the participants do not want to allow are different in the countries. In comparison to the already downloaded applications and declarations against the permits requested without naming the application, it is understood that citizens living in the UK are more likely to avoid taking risks than citizens living in the United States and Turkey. It has also emerged as an important finding of denial of application permit request at a high rate seen in all countries. Because people avoid reading individual permissions and because the requested permissions become routine after a certain period of time, differences can arise during the course of the activities with the risk attitudes of people in daily life. This can lead to questions about the sharing and protection of personal information.
Keywords: Mobile Application Permission; Risk Attitude; Data Security; Mobil Uygulama İzni; Risk Tutumu; Veri Güvenliği